2018
DOI: 10.1371/journal.pcbi.1006079
|View full text |Cite
|
Sign up to set email alerts
|

Biobeam—Multiplexed wave-optical simulations of light-sheet microscopy

Abstract: Sample-induced image-degradation remains an intricate wave-optical problem in light-sheet microscopy. Here we present biobeam, an open-source software package that enables simulation of operational light-sheet microscopes by combining data from 105–106 multiplexed and GPU-accelerated point-spread-function calculations. The wave-optical nature of these simulations leads to the faithful reproduction of spatially varying aberrations, diffraction artifacts, geometric image distortions, adaptive optics, and emergen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…The beam propagation method (BPM) represents an extension to the propagator approach which uses approximations but works in optically inhomogeneous media. The BPM has been used in a software package termed BioBeam that simulates light propagation through optically inhomogeneous media both in the illumination and detection path for different light sheet types at greatly improved speed by relying on a GPU [29]. In principle, our analysis can be readily applied to BioBeam results as well as to assess performance in inhomogeneous media.…”
Section: Discussionmentioning
confidence: 99%
“…The beam propagation method (BPM) represents an extension to the propagator approach which uses approximations but works in optically inhomogeneous media. The BPM has been used in a software package termed BioBeam that simulates light propagation through optically inhomogeneous media both in the illumination and detection path for different light sheet types at greatly improved speed by relying on a GPU [29]. In principle, our analysis can be readily applied to BioBeam results as well as to assess performance in inhomogeneous media.…”
Section: Discussionmentioning
confidence: 99%
“…The beam propagation method (BPM) represents an extension to the propagator approach which uses approximations but works in optically inhomogeneous media [12]. The BPM has been used in a software package termed BioBeam that simulates light propagation through optically inhomogeneous media both in the illumination and detection path for different light sheet types at greatly improved speed by relying on a GPU [29]. In principle, our analysis can be readily applied to BioBeam results as well to assess performance in inhomogeneous media.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of GPUs and GPU clusters along with the proposed quantized rotation-based OVSS system may make the system even faster. It is reported that, GPUs can further accelerate volume imaging 56 . Moreover, the use of multiple CPUs and optionally GPU has accelerated the reconstruction process in less than a 15 min on a NVdia P6000 graphics board 57 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the use of multiple CPUs and optionally GPU has accelerated the reconstruction process in less than a 15 min on a NVdia P6000 graphics board 57 . Specifically, Biobeam computational software based on GPU implementations has substantially reduced volume reconstruction time 56 . Current state-of-the-art light-sheet microscopes requires a lot of precious data-acquisition time that severely slows down the imaging process 58 , 59 .…”
Section: Discussionmentioning
confidence: 99%